The Hadith View of Ibn ‘Arabī in His Kitab Mishkat Al-Anwar - Nabil Amir, Ahmad; Abdul Rahman, Tasnim (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2026)
This paper analyzes Muhyīddīn Ibn ‘Arabī’s (1165-1240) seminal work Mishkāt al-Anwār fī mā Ruwiya ‘an Allāh min al-Akhbār (101 Divine Sayings), which compiles profound sacred hadiths (hadith qudsī) transmitted from God through the Prophet Muhammad. It aims to examine its theological implications and mystical conceptions of God, which brought forth diverse religious themes underlying its arguments pertaining to the moral and religious values and symbols that constituted basic ritual and legal practice and its spiritual and mystical implications as highlighted by the Great Master Shaykh al-Akbar throughout this work. The study is based on qualitative method in the form of library and literature survey. It uses descriptive, analytical, philosophical and historical approaches to collectively process the data derived from primary and secondary sources that were further objectively and scientifically analyzed. The study concludes that Mishkāt al-Anwār presents significant ideas and understanding of sacred hadith (hadith qudsī) and its broad ethico-legal and mystical conception in light of the synthetic ideology it brought forth that synthesize dogmatic orthodoxy and liberal sufi tradition. It set forth profound metaphysical and eschatological principle and value as well as its spiritual aspect and dimension in light of prophetic guidance derived from revealed law and its sacred interpretation and viewpoint. It reflected unprecedented allegorical and mystical connotation of the Divine Sayings, in light of the Word of God that inspired the light of prophetic reality and its metaphysical manifestation.